Small molecule inhibitor agerafenib effectively suppresses neuroblastoma tumor growth in mouse models via inhibiting ERK MAPK signaling. (10th August 2019) - Li, Hui; Yu, Yang; Zhao, Yanling; Wu, Deanna; Yu, Xiaoman; Lu, Jiaxiong; Chen, Zhenghu; Zhang, Huiyuan; Hu, Yongguang; Zhai, Yuanfen; Su, Jun; Aheman, Ayinuer; et al.
Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor in early childhood. Despite intensive multimodal therapy, nearly half of children with high-risk disease will relapse with therapy-resistant tumors. Dysregulation of MAPK pathway has been implicated in the pathogenesis of relapsed and refractory NB patients, which underscores the possibility of targeting MAPK signaling cascade as a novel therapeutic strategy. In this study, we found that high expressions of RAF family kinases correlated with advanced tumor stage, high-risk disease, tumor progression, and poor overall survival. Targeted inhibition of RAF family kinases with the novel small molecule inhibitor agerafenib abrogated the activation of ERK MAPK pathway in NB cells. Agerafenib significantly inhibited the cell proliferation and colony formation ability of NB cells in vitro, and its combination with traditional chemotherapy showed a synergistic pro-apoptotic effect. More importantly, agerafenib exhibited a favorable toxicity profile, potently suppressed tumor growth, and prolonged survival in NB mouse models. In conclusion, our preclinical data suggest that agerafenib might be an effective therapeutic agent for NB treatment, both as a single-agent and in combination with chemotherapy. Highlights: RAF overexpression correlates with poor prognosis in NB patients. Agerafenib abrogates the ERK MAPK signaling pathway activation in NB cells. Agerafenib suppresses NB cell proliferation and anchorage-independent growth in vitro. Agerafenib synergizes with chemotherapeutic agent and enhances doxorubicin-induced apoptosis in resistant NB cell lines. Agerafenib exhibits a favorable toxicity profile, potently inhibits tumor growth, and prolongs survival in NB mouse models.